Financial Algorithms for Dynamic Investment Reallocation - Alfranso, Lindsey (2012)
This dissertation provides the fundamentals of dynamic investment reallocation and their applications to trading investment practitioners’ decisions in the financial services sector. Our objective is to explain the concepts and techniques that can be applied to real-world dynamic investment decision making. While empirical findings on dynamic reallocation in investment theory are currently limited, we take a bold step towards a new approach to allocation in respect to trading investments. We develop a dynamic reallocation model to explore its implications for allocators. We present our findings in a way which poses questions as to the importance of further research in this field. We explore the findings of both simulated and published data to derive important conclusions.